Enhancing data transfer architecture using LSB steganography combined with reed solomon code - A. Jassim, H; K. Taha, Z; A. Alsaedi, M; M. Albaker, B (International Journal of Engineering and Technology, 2018)
In this paper, new steganographic systems employing least significant bit technique and wavelet transform for embedding are proposed. These systems incorporate threshold level technique to enhance the performance of embedding scheme. Further, Forward error correcting code is used to improve the system performance. In the proposed system, the cover image is a gray image and the wavelet transform is applied directly. The secret image is coded using Reed Solomon code for preparing to embedding process. The locations of embedding are randomly selected according to pseudorandom number sequence. The combination between the ciphering process and steganography gives the system high level of security. This idea makes unauthorized retrieval is difficult. The simulation results show that the stego image is visually similar to the original one and does not have any suspension about embedded image. The extracted secret image is similar to the original secret image. The results indicate that using one-level Haar wavelet transform increases the capacity of the secret image that can be embedded. Hence, the steganographic goals are achieved in these systems. The proposed systems are simulated using MATLABÂ® software package.Â Â